Genetic ablation of lymphocytes and cytokine signaling in nonobese diabetic mice prevents diet‐induced obesity and insulin resistance. Issue 3 (7th December 2015) - Friedline, Randall H.; Ko, Hwi Jin; Jung, Dae Young; Lee, Yongjin; Bortell, Rita; Dagdeviren, Sezin; Patel, Payal R.; Hu, Xiaodi; Inashima, Kunikazu; Kearns, Caitlyn; Tsitsilianos, Nicholas; Shafiq, Umber; et al.
Abstract : Obesity is characterized by a dysregulated immune system, which may causally associate with insulin resistance and type 2 diabetes. Despite widespread use of nonobese diabetic (NOD) mice, NOD with severe combined immunodeficiency ( scid ) mutation (SCID) mice, and SCID bearing a null mutation in the IL‐2 common g chain receptor (NSG) mice as animal models of human diseases including type 1 diabetes, the underlying metabolic effects of a genetically altered immune system are poorly understood. For this, we performed a comprehensive metabolic characterization of these mice fed chow or after 6 wk of a high‐fat diet. We found that NOD mice had ~50% less fat mass and were 2‐fold more insulin sensitive, as measured by hyperinsulinemic‐euglycemic clamp, than C57BL/6 wild‐type mice. SCID mice were also more insulin sensitive with increased muscle glucose metabolism and resistant to diet‐induced obesity due to increased energy expenditure (~10%) and physical activity (~40%) as measured by metabolic cages. NSG mice were completely protected from diet‐induced obesity and insulin resistance with significant increases in glucose metabolism in peripheral organs. Our findings demonstrate an important role of genetic background, lymphocytes, and cytokine signaling in diet‐induced obesity and insulin resistance.—Friedline, R. H., Ko, H.J., Jung, D. Y., Lee, Y., Bortell, R., Dagdeviren, S., Patel, P. R., Hu, X., Inashima, K., Kearns, C., Tsitsilianos, N., Shafiq, U., Shultz, L. D., Lee, K. W., Greiner, D. L., Kim, J. K., Genetic ablation of lymphocytes and cytokine signaling in nonobese diabetic mice prevents diet‐induced obesity and insulin resistance. FASEB J. 30, 1328–1338 (2016). www.fasebj.org